Use of "rectangular grid" code for permutation key generation - Жвалюк, Юлія Андріївна; Грицюк, Юрій Іванович (Ukrainian Information Security Research Journal, 2013)
In the complicated algorithms of today are widely used rearranging ciphers that use a rectangular table. The essence of cryptographic transformation in such ciphers are that the symbols of the original message are entered in the cells of the table following a route, and then – the symbols are write out in a different route from it. Such codes are called ciphers of route rearranging. It was determined that "rectangular grid" code is route permutation algorithm, in which a rule placing symbols in the block is given by a rectangular stencil, can be used not only to encrypt the message block, but also for permutation key generation. Using core provisions of the matrix al-gebra the mathematical formulation of the "rectangular grid" cipher for permutation key generation, as well as mathematical formulation of the permutation algorithm of matrix columns of the original message, the number of rows which can be random, were developed.